The Representation of Duration In Jacques Villon’s Cubist Printmaking works (Damascus University Journal for engineering sciences, 2022)
Cubism was the most important aesthetic revolution in modern art, with which the shift towards abstract geometric vision began, starting with Cézanne's experiences in his post-impressionist epoch. Cubism's ideas were shaped by the profound influence on its artists of the idealistic philosophy that has prevailed in European cultural circles since the late 19th century, and have answered the appeal of the human spirit in its superiority over material. The idea of Duration is a systematic ideal basis in understanding the transformation that led to the emergence of cubist vision through the Pergsonian intuitive approach that influenced Cézanne and Cubists. At this period, the techniques of printmaking formed a creative expressive medium that met the expressive and shaping need of the modernist artist. The research will therefore try to study the aesthetics of duration in printmaking artwork through Jacques villon's cubist experience
Keywords: Representation; Duration; Printmaking; Cubism; Intuition; Jacques Fillon; Geometric idealism